The Southern Farmers' Alliance, Populists, and lynching. Issue 1 (17th November 2023) - Chamberlain, Adam; Yanus, Alixandra B.
Abstract: The lynching literature often considers how the Populist Party affected lynching, yet the Southern Farmers' Alliance—a short-lived but influential voluntary association that mobilized large numbers of white farmers—is overlooked. We argue that this is a critical oversight, as the Alliance was the origin of populism in the South. Specifically, we hypothesize that where the Alliance had more local organizations, the greater the likelihood of lynching from 1888 to 1895, the peak period of populism. To test this, we focus on two states with different experiences with the Alliance: North Carolina, in which the state's Alliance was a strong supporter of the Populist Party, and South Carolina, where the Democrats sought to court Alliancemen and deter the creation of, and voting for, the Populist Party. Our empirical findings reveal that lynchings were more common in counties where the Farmers' Alliance had more organizations in South Carolina, but no similar connection exists in North Carolina. These findings suggest that the Southern Farmers' Alliance is, at times, pivotal to understanding populism's connection to lynching in the late-nineteenth century American South.